Classifying Cardiac Actin Mutations Associated With Hypertrophic Cardiomyopathy - Despond, Evan A.; Dawson, John F. (Frontiers in Physiology, 2018)
Mutations in the cardiac actin gene (ACTC1) are associated with the development of hypertrophic cardiomyopathy (HCM). To date, 12 different ACTC1 mutations have been discovered in patients with HCM. Given the high degree of sequence conservation of actin proteins and the range of protein-protein interactions actin participates in, mutations in cardiac actin leading to HCM are particularly interesting. Here, we suggest the classification of ACTC1 mutations based on the location of the resulting amino acid change in actin into three main groups: 1) those affecting only the binding site of the myosin molecular motor, termed M-class mutations, 2) those affecting only the binding site of the tropomyosin regulatory protein, designated T-class mutations, and 3) those affecting both the myosin- and tropomyosin-binding sites, called MT-class mutations. To understand the precise pathogenesis of cardiac actin mutations and develop treatments specific to the molecular cause of disease, we need to integrate rapidly-growing structural information with studies of regulated actomyosin systems.